Adding 9 to both sides of the equation:
-3x - 9 + 9 = -21 + 9
-3x = -12
Dividing both sides by -3:
x = -12 / -3
x = 4
The equation −3x−9=−21
is solved as follows. Supply the correct numbers to complete the solution.(1 point)
−3x−9=−21
−3x=
Add 9 to both sides.
x=
Divide both sides by −3
.
3 answers
The equation 10x+13=−12
is solved as follows. Supply the correct numbers to complete the solution.(1 point)
10x+13=−12
10x=
Subtract 13 from both sides.
x=
Divide both sides by 10.
is solved as follows. Supply the correct numbers to complete the solution.(1 point)
10x+13=−12
10x=
Subtract 13 from both sides.
x=
Divide both sides by 10.
Subtracting 13 from both sides of the equation:
10x + 13 - 13 = -12 - 13
10x = -25
Dividing both sides by 10:
x = -25 / 10
x = -2.5
10x + 13 - 13 = -12 - 13
10x = -25
Dividing both sides by 10:
x = -25 / 10
x = -2.5